Durable Polymer Coatings: A Comparative Study of PDMS-Based Nanocomposites as Protective Coatings for Stone Materials - Maduka L. Weththimuni; Marwa Ben Chobba; Donatella Sacchi; Mouna Messaoud; Maurizio Licchelli (Chemistry, 2022)
Nowadays, durable protective coatings receive more attention in the field of conservation for several reasons (they are cost effective, time consuming, more resistance, etc.). Hence, this study was focused on producing a multi-functional, durable coating to protect different stone materials, especially, Lecce stone, bricks, and marble. For this purpose, ZrO2-doped-ZnO-PDMS nanocomposites (PDMS, polydimethylsiloxane used as the binder) were synthesized by in situ reaction (doped nanoparticles were inserted into the polymer matrix during the synthesis of PDMS) and the performances of resulting coatings were examined by handling different experimental analyses. In particular, the study aimed to evaluate the durability properties of the coating along with the self-cleaning effect. As a result, the durability of the nanocomposite coating with respect to the well-known PDMS coating was assessed after exposure to two different ageing cycles: solar ageing (300 W, 1000 h) and humid chamber ageing (RH > 80%, T = 22 ± 3 °C, desiccator, 2 years). All the results were in good agreement with each other providing that newly prepared nanocomposite coating can be used as a durable protective coating for different stone materials.